2018
DOI: 10.3390/ijerph15122871
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Basic Psychological Needs in Exercise Settings: An Examination of Differences in Contextual Motivation, Affect, and Achievement Goals

Abstract: Understanding leisure-time physical activity is vital for a healthy world. It is well known that physical activity has positive effects on psychological health, but further evidence is required to ascertain how different environments influence positive behavioral outcomes. Thus, the aim of this study was to examine the differences in contextual motivation, affect, and achievement goals according to profiles of basic psychological needs in adult exercisers. The sample consisted of 401 young adult exercisers ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
(64 reference statements)
1
1
0
3
Order By: Relevance
“…The negative correlation between basic psychological needs and amotivation is consistent with previous research [38,72], indicating that when elite college skiers perceive their needs as unmet or frustrated, they are more likely to experience a lack of motivation or indifference towards skiing. This nding is in line with the concept of amotivation, which refers to a state of lacking any motivation or intention to engage in an activity.…”
Section: Basic Psychological Needs and Motivationsupporting
confidence: 90%
“…The negative correlation between basic psychological needs and amotivation is consistent with previous research [38,72], indicating that when elite college skiers perceive their needs as unmet or frustrated, they are more likely to experience a lack of motivation or indifference towards skiing. This nding is in line with the concept of amotivation, which refers to a state of lacking any motivation or intention to engage in an activity.…”
Section: Basic Psychological Needs and Motivationsupporting
confidence: 90%
“…The person‐centered approach has proven useful to better understand motivational differences and associated consequences in various fields. In sports (Cetinkalp & Lochbaum, 2018; Fernandez‐Ozcorta et al, 2019; Kazak, 2018) and elderly care (Almagro et al, 2012; Souesme et al, 2016; Vanhove‐Meriaux et al, 2018), two or three basic needs clusters were identified and dedicated recommendations made to improve coaching and care protocols. Analyzing secondary school students' relatedness to peers and teachers, Leon and Liew (2017) distinguished four clusters.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Bu konudaki literatürün çok büyük bir kısmı da üç temel psikolojik ihtiyacın tatmininin hür iradeli güdüsel yönelim ve içsel düzenleme ile pozitif ilişkili olduğu yönündedir (Dysvik vd., 2013;Sibley ve Bergman, 2018). Önceki çalışmalar, içsel düzenlemenin üç temel psikolojik ihtiyaç ile olumlu ilişkisinden dolaylı görev yönelimi ile olumlu ilişkili olacağını savunmuştur (Hagger ve Chatzisarantis, 2008;Kazak, 2018). Spor ortamında temel psikolojik ihtiyaçlar, motivasyonel düzenlemeler ve hedef yöneliminin birlikte araştırıldığı, Álvarez ve ark., (2009)' nın futbolcular üzerinde yapmış oldukları araştırmada üç temel psikolojik ihtiyaç ile görev yönelimi ve içsel düzenleme arasında pozitif ilişki bulunmuştur.…”
Section: Tartışma Ve Sonuçunclassified
“…Reinboth ve da üniversiteli sporcular üzerinde yaptıkları araştırmada görev yöneliminin psikolojik ihtiyaçlar ile pozitif yönde ilişkili olduğunu belirtmişlerdir. Kazak (2018) tarafından egzersiz katılımcılarında görev yönelimi ve temel psikolojik ihtiyaçlar arasındaki ilişkinin araştırıldığı çalışmada da benzer şekilde görev yönelimi ile temel psikolojik ihtiyaçlar arasında orta düzeyde pozitif ilişki tespit edilmiştir. Bu çalışmalardan elde edilen bulgular araştırmamızı destekler niteliktedir.…”
Section: Tartışma Ve Sonuçunclassified
See 1 more Smart Citation